The long-term injured competitive athlete: A study of psychosocial risk factors. - Johnson, U. (1997)
The thesis includes five separate studies concerned mainly with psychosocial aspects of the problems that athletes afflicted with long-term sport injuries face. The first study deals with relationships between personality variables, coping strategies and mood-levels, both in athletes participating in competitive sports and in a non-athlete reference groups. The results indicate the athletes to use emotionally oriented coping strategies to a greater extent than the non-athletes. The results also point to a somewhat higher degree of extrovert behaviour in the athlete group. The male athletes tended to rely more strongly on self-confidence and humour than the female athletes did. The second study aimed at investigating possible differences in personality and coping strategies between competitive-level athletes with long-term injuries and a matched non-injured group. No differences between the groups were found in terms of basic personality traits. Being injured was associated, however, with a depressed mood state and with activation of coping strategies directed at receiving help from others. The injured men had greater confidence in their ability to handle stressful situations, whereas the injured women showed a stronger inclination to use emotionally oriented coping strategies. Team-sport athletes were found to cope more in terms of the "passive acceptance" of help from others than individual-sport athletes did. The third study aimed at comparing multiply-injured athletes with first-time injured athletes in terms of patterns of adaptation. In contrast to earlier research, results of the present study suggested previous experience or lack of experience with serious sport-injuries to govern the rehabilitation process to a greater extent than various relevant personality traits did. First-time injured athletes tended to experience the rehabilitation period as more stressful than multiply-injured athletes did and, in agreement with assessments by their physiotherapists, did not regard themselves as being physically restored after rehabilitation. The fourth study aimed at detecting possible psychosocial risk factors during rehabilitation through a close examination of 81 long-term injured athletes' experience of being injured. For athletes dropped out due to severe and complex injuries, it was found that, 10 month after the end of rehabilitation, seven of the 77 athletes (9%) had not returned to their sport, despite a favourable physical prognosis. At the beginning of rehabilitation six of this athletes experienced the fact of being injured as highly stress- and anxiety-provoking. They were also characterized by low hedonic tone, both initially and at the end of rehabilitation, by a proneness to rely on external support, by low ratings on the coping strategies of self-confidence and humour, and by limited goals or guidelines concerned with their making a comeback. The fifth study, finally, in a further effort to pinpoint psychosocial risk factors during and after rehabilitation, followed up the seven athletes who 10 months after the end of rehabilitation had not returned to their usual level of physical activity despite a favourable physical prognosis (non-returning group). An additional aim was to study how early in the rehabilitation process it is possible to identify and predict different patterns of adaptation. The non-returning athletes were found to not have returned to their sport even at the last follow-up some 3 years after their injury. Logistic regression analysis revealed, already on the first test occasion at the very beginning of the rehabilitation, a distinct pattern of risk markers that could be used to identify the non-returning athletes. Ominous signs here were the following: insufficient mental planning for rehabilitation, a predominantly negative attitude toward rehabilitation, restricted social contact with former club mates and low hedonic tone.